Effect of component dismantling on quality of sterilization of mechanical torque limiting devices (pilot study) - Saboury, Aboulfazl; Sadr, Seyed Jalil; Eslami, Gita; Rashidpour, Mahsa; Ahmad Nejad, Mohammad Ebrahim; Mahshid, Minoo; Najari Dizaji, Nazila; Fayyaz, Ali (Journal of Dental School, 2019)
Objectives Dental instruments may serve as a route of infection transmission. The necessity of dismantling of Friction-Style (FS) and Spring- Style (SS) mechanical torque limiting devices (MTLDs) prior to disinfection and sterilization is a matter of debate, aside fromthe fact that it is difficult and time-consuming. This study sought to assess the effect of dismantling of components on quality of sterilizationof MTLDs. Materials and Methods This in vitro experimental study was performed on 96 torque devices. Forty eight FS-MTLDs of two manufacturers (n = 24) namely Astra Tech (Hader SA, La Chaux-de-Fonds, Switzerland) and Dr. Idhe (Dr. Idhe Dental, Eching, Munich, Germany) and 48 SS-MTLDs of two manufacturers (n = 24) namely Nobel Biocare (Nobel Biocare, Goteborg, Sweden) and Straumann (Institut Straumann, Basel, Switzerland). After coding, specimens were inoculated with Bacillus stearothermophilus (PTCC1713) and 24 devices of four manufacturers each were divided into two groups (n = 12) for disinfection in assembled or disassembled form. Each group was then divided into two subgroups (n = 6) for sterilization in assembled or dismantled form. After disinfection and sterilization, bacterial proliferation was assessed for all MTLDs. In case of observing turbidity, Gram-staining and differential tests were performed. The results were expressed as presence or absence of contamination. Results Growth of B. stearothermophilus did not occur in any plate (no turbidity). Only one plate showed growth of Staphylococcus saprophyticus. Conclusion Dismantling of components had no significant effect on quality of sterilization of MTLDs.